Design and construction of an electrolytic multi electrode reactor for laboratory - Arias, Vladimir (2011)
The construction of an electrolytic reactor for its use in a laboratory with the possibility of varying the number of electrodes, simultaneously the volume capacity of the electrolytic, and its application to a gamma of electrosynthesis process, has determined the election of a rectangular model, so in this way it can be defined the operative variables when addressing a specific process. The job requirements were taken into account during the design, which were the operational simplicity, the maintenance reliability, and the faculty to fit easily taking into account all the involved costs. Therefore, the election of a filter press type modular cell will allow increasing the number of electrodes and the capacity as it is required, without changing its dimensions.